(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the pedagogical significance of improving innovative and integrative technologies in the preparation of future primary school teachers. The study is based on the idea that contemporary teacher education can no longer be limited to the transfer of separate methodological skills or fragmented digital competencies. The professional formation of a primary teacher requires a coherent model in which pedagogical knowledge, subject knowledge, technological literacy, reflective practice, interdisciplinary thinking, and value-oriented educational responsibility are developed as a unified system. The article argues that innovative technologies in teacher education should not be understood only as digital tools, platforms, or interactive devices. Their real educational value emerges when they are integrated into meaningful pedagogical design, collaborative inquiry, microteaching, school-based practice, formative assessment, and problem-solving activities. In this context, integrative technologies are interpreted as technologies that connect theory with practice, university coursework with classroom realities, and different subject areas with one another. Special attention is paid to the preparation of future primary school teachers because primary education demands flexibility, child-centeredness, creativity, and the ability to organize learning across multiple disciplines. The article identifies the main contradictions in current teacher preparation, including the gap between technical familiarity and pedagogical readiness, the overemphasis on tools rather than learning goals, and the insufficient coordination between university training and school innovation.